Multiple intelligences around the world - Chen, Jie-Qi.; Moran, Seana; Gardner, Howard (San Francisco : Jossey-Bass, 2009)
Multiple intelligences (MI) theory has been introduced and implemented successfully in numerous countries around the world. This is the first collection to review, synthesize, and reflect on this unique cross-cultural and educational phenomenon. Through this synthesis and reflection, the book's authors provide a fresh and fuller understanding of MI theory. In addition, they develop more specific knowledge about why MI theory has been welcomed in so many countries, how its use can be appropriate in diverse cultures, and what has supported and fueled travel of the MI meme.
Includes bibliographical references and indexes.
Keywords: Multiple intelligences -- Cross-cultural studies